Cyclic Fatigue Resistance and SEM Evaluation of Fractured Instrument Surfaces; Comparison of ProTaper Universal and ProTaper Gold Files - Meltem Öztan; Emine Odabaşı Tezer; Nilgün Barut (Ankara University, 2022)
Purpose:To compare the cyclic fatigue resistance of ProTaper Universal (PTU) and ProTaper Gold (PTG) nickel titanium files at different angles and to examine the fractured surface areas by using scanning electron microscope (SEM). Materials and Methods: A special static test device made of stainless steel with artificial canals at 3 different angles. The files were rotated until they were broken in artificial canals with 45°, 60° and 90° angles and also the time was recorded using a digital stopwatch. The number of cycles to failure was calculated for each instrument. Statistical analyzes were made by using one-way analysis of variance (Anova) for comparison between main groups. Results: PTG files showed higher fatigue resistance (p